2018
DOI: 10.1002/aoc.4581
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of VO2+, Co2+, Ni2+, Cu2+ and Zn2+ Complexes of a Schiff base ligand derived from ethyl 2‐amino‐6‐ethyl‐4,5,6,7‐tetrahydrothieno[2,3‐c]pyridine‐3‐carboxylate and their Investigation as fungicide Agents

Abstract: Complexes of VO 2+ , Co 2+ , Ni 2+ , Cu 2+ , and Zn 2+ ethyl-6-ethyl-2-((2hydroxybenzylidene)amino)-4,5,6,7-tetrahydrothieno[2,3-c]pyridine-3-carboxylate were synthesized and characterized via different spectroscopic techniques.The whole results declared that the complexes assembled in 1:1 mole ratio furthermore, the spectroscopic data analysis proved the present ligand adhered to the different metal ions in neutral or monobasic tridentate ligand via azomethine nitrogen, carbonyl oxygen atoms and protonated/de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…The antimicrobial studies indicated that all the metal chelates exhibited significantly enhanced activity against microbial strains in comparison to the free ligand. Previous studies elsewhere suggested that chelation tended to make the chelates perform as more powerful and potent bacteriostatic agents, thus inhibiting the growth of microbes more than the parent ligands did, and is similar to that of this study. It was suspected that factors such as solubility, conductivity, dipole moment and cell permeability mechanism influenced by the existence of metal ion might be the possible cause of the increase in activity.…”
Section: Resultssupporting
confidence: 88%
“…The antimicrobial studies indicated that all the metal chelates exhibited significantly enhanced activity against microbial strains in comparison to the free ligand. Previous studies elsewhere suggested that chelation tended to make the chelates perform as more powerful and potent bacteriostatic agents, thus inhibiting the growth of microbes more than the parent ligands did, and is similar to that of this study. It was suspected that factors such as solubility, conductivity, dipole moment and cell permeability mechanism influenced by the existence of metal ion might be the possible cause of the increase in activity.…”
Section: Resultssupporting
confidence: 88%
“…[ 57,58 ] The sulfato complexes IR spectra of ( 2 ) and ( 8 ) disclosed two bands at 1,129, 1,055 and 1,117, 1,048 cm −1 consecutively ascribing to the uni‐chelated sulfate group, which was proofed by their low conductivity values. [ 26,59 ] In case of VO 2+ complex ( 2 ), a new band was sighted at 945 cm −1 , which is attributable to ν(V=O). [ 53 ]…”
Section: Resultsmentioning
confidence: 99%
“…[18] Pilichos et al studied the coordination and metal ion-mediated transformation of a polydentate ligand containing oxime, hydrazone, and picolinoyl functionalities [19] while Drover et al described the preparation and characterization of tetranuclear, binuclear, and chain complexes with a hydrazone-oxime and hydrazone series. [20] Because of the interesting bioactivities of compounds incorporating both oxime and hydrazone moieties and for continuing of our previous work to explore the biological activities of metal complexes, [21][22][23][24][25][26] this research was devoted to the synthesis of new hydrazone-oxime derived from 2,4,6-trichlorophenyl hydrazine and its Cd 2+ , Zn 2+ , Cu 2+ , Ni 2+ , Co 2+ , Fe 3+ , Mn 2+ , and VO 2+ complexes. The investigation of prepared compounds structure was done via spectral, analytical, and theoretical techniques such as infrared (IR), nuclear magnetic resonance (NMR), mass, electron spin resonance (ESR), and electronic absorption spectrum (EAS) as well as elemental, thermal and density functional theory (DFT) studies in addition to the magnetic and molar conductance measurements for complexes.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Schiff base complexes have gained considerable attention due to their remarkable biological abilities (such as antibacterial, anti‐inflammatory, antioxidant, and antiviral activities). [ 4–6 ] Schiff bases comprising heterocyclic rings have gained a great attention, because of their possibilities as ligands and the ability to bind multiple biological targets. [ 7 ] One of heterocycles, the furfuryl amine component constitutes an easily accessible nucleus that is present in a number of natural and pharmacological compounds.…”
Section: Introductionmentioning
confidence: 99%